Juxtaposing Pakistani diaspora policy with migrants' transnational citizenship practices. (November 2016) - Erdal, Marta Bivand
Highlights: The Pakistani state's diaspora policies are juxtaposed with migrants' practices. Migrants' transnational citizenship practices also encompass formal citizenship(s). Overlaps, friction, and disruptions emerge in stories of 'peoplehood'. The elusive nature of residency contributes to complicating (formal) citizenship. The (emigration) state's extent of power to define 'peoplehood' has limits. Abstract: Through a juxtaposition of diaspora policy with migrants' transnational citizenship practices, this article explores how peoplehood, nationhood and citizenship are articulated, justified and enacted. The article draws on the politico-spatial context of Norwegian-Pakistani transnational social space, analyzing the Pakistani Origin Card (POC), remittances and return mobilities as transnational citizenship practices. The elusiveness of residency becomes apparent, underscoring the salience of territoriality, for both diaspora strategies and transnational citizenship practices, involving the co-constitution of formal membership and everyday citizenship practices. Through this overlaps, frictions and disruptions in conceptions of citizenship and of nationhood are revealed, underscoring their non-static nature. Whilst questions of who is included within the people are more commonly approached from the vantage point of immigration contexts, they share key tenets of struggles over conceptualizations of citizenship, and more plural ideologies of nationhood, in emigration contexts, exposed by a juxtaposition of diaspora policies and migrants' transnational citizenship practices.